Responding to the Popular Demand: Itinerary for the Socio-Political Learning of Situated Agroecologies in Chile - Peredo-Parada, S; Barrera-Salas, C (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Agroecology has proven to be successful in responding to the demands and needs of a collective due to the relevance of its approach and proposals, which are built collaboratively between all the actors under a specific context that focuses on the actions developed. This is facilitated when spaces of horizontal interaction are generated through dialogues between different perspectives and experiences. In this perspective, agroecological training in higher education, i.e., university level, requires structural changes that go beyond the incorporation of technical content. Based on a critical documentary analysis of the records generated in the implementation of teaching innovation projects, the learning itinerary in agroecology is presented, consisting of four certifications based on transformational learning and supported by active methodologies. The potentialities, including marketing potential, of the proposed learning itinerary relate to curricular design, the articulation of the itinerary, the suitability of the learning methodologies used, the performance of the teachers, and the participation of the students. It is concluded that the implementation of flexible itineraries allows for addressing the transformation processes necessary for an agroecological transition in which we see a convergence of students’ skills, the learning objectives, and the requirements of the various actors with which they interact. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.